SAPHO Syndrome Complicated by Ankylosing Spondylitis Successfully Treated With Tofacitinib: A Case Report - Yuan, Fangfang; Luo, Jing; Yang, Qiong (Frontiers in Immunology, 2022)
Abstract Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome, a type of chronic inflammatory disease, is rare and difficult to treat. Osteoarthropathy with skin involvement is the primary clinical manifestation of SAPHO syndrome. The unknown pathogenesis of SAPHO syndrome is speculated to be related to individual genetic differences, immune levels, microorganisms, and environmental factors. Tofacitinib, a novel small-molecule Janus kinase (JAK) inhibitor, has been used to treat rheumatoid arthritis. However, it also has great potential for the treatment of other immune diseases, including SAPHO syndrome. A 36-year-old man with chest and back pain for more than two months was admitted to our hospital. After admission, the patient developed a pustular rash and enteritis. SAPHO syndrome was diagnosed based on the above clinical manifestations, computed tomography (CT), and bone scintigraphy findings. Notably, the patient also had ankylosing spondylitis. Tofacitinib significantly improved the patient’s skin symptoms while preventing worsening of chest and back pain when adalimumab was discontinued. We report the first case of ankylosing spondylitis with SAPHO syndrome. In addition, it is also the first successful treatment thereof with tofacitinib. We hope to provide valuable information regarding the pathogenesis and treatment of SAPHO syndrome in this case.